Prevalence of C-shaped root canals in Iranian population: a systematic review. - Mandana Naseri; Ali Kangarlou Haghighi; Mohammad Javad Kharazifard; Atefeh Khavid (Tehran University of Medical Sciences, 2013)
Because of the great challenges in the diagnosis and treatment of "C" configuration and lack of any systematic information about its occurrence, the purpose of the present study is to determine the prevalence of C shaped root canals in Iranian population.An exhaustive search was undertaken to identify published and unpublished researches related to the C-shaped canals by using key words. The search of the MEDLINE database included all publications from 1966 to May 2012.Then selected articles were obtained and reviewed. Data evaluated and summarized in the data sheet included methodology, population, number of teeth per study (power), number of root canals, type of root canal configuration, and c-shaped canals.Six studies were included with total of 1062 teeth, all in mandibular second molars. The total incidence of C-shaped canals in Iranian population was obtained 6.96%.The incidence of C-shaped canals in Iranian population is 6.96%, which seems much less than Asian populations but nearer to Middle East countries.